Association between extracellular DNA levels, markers of inflammation and left ventricular mass index in children with chronic kidney disease - Ylva Tranæus Lindblad; Ľubomíra Tóthová; Peter Celec; Karolina Kublickiene; Peter Bárány; Milan Chromek (Scientific Reports)
Abstract Chronic kidney disease (CKD) is associated with chronic low-grade inflammation, but the primary factors triggering this inflammation remain unclear. Extracellular or cell-free DNA (exDNA) originates from virtually all tissues, being released during cell death, and stimulates the innate immune system. Our study was designed as an observational, cross-sectional cohort study of children with CKD (both before and after kidney transplantation) and controls to analyze associations between exDNA, markers of inflammation, and cardiovascular health. Extracellular DNA (total, nuclear, and mitochondrial) was analyzed in plasma using fluorometry and real-time PCR. We found that children with CKD after kidney transplantation had higher concentrations of total and nuclear extracellular DNA (total exDNA and nc_exDNA) in plasma compared to controls. In univariate analysis, levels of interleukin-6 (IL-6), antimicrobial peptide cathelicidin (LL-37), soluble vascular cell adhesion molecule-1 (VCAM-1) and left ventricular mass index (LVMI) were positively correlated with total exDNA and nc_exDNA concentrations. Multivariate analysis revealed LVMI as the only independent variable associated with high levels of both total exDNA and nc_exDNA. We believe that our results contribute new knowledge to the pathogenesis of CKD and its complications and may help identify new treatment targets.